O processo de distribuição de cargas : determinação de rota ótima através da comparação entre algoritmos AHP/FUZZY e multicritério - Leonardo, Izabel Cristina de Melo (2019)
This thesis aims to determine an optimal route for load distribution in terms of efficiency and effectiveness by comparing two algorithms, both developed for the present work as support for decision making. The multicriteria algorithms, when elaborated in a fuzzy model, allow to analyze subjective aspects of the problem, adding more details to the script. Distribution is carried out by road in nine Brazilian locations, according to existing limitations. Currently, road transport has the highest concentration in the country’s transportation matrix; given this scenario, this thesis seeks to generate an impact on the economy through the reduction of logistics costs and process improvement, allowing greater business competitiveness.